Availability, Usability, and Effectiveness of Technological Gadgets in Teaching Sport Psychology for Sustainable Global Development in Tertiary Institutions - Sunmonu, Mathew Sonayon; Oyekunle, Abimbola Oluwatosin; Adesanya, Adeyemi Taofik; Honawon, Nunayon Phillip (Faculty of Natural and Applied Sciences Journal of Computing and Applications, 2025)
The advent of new technologies in the world has significantly altered the progression of sporting achievements; sports have become increasingly important for recording, analysing and optimising athletic performance. The integration of technological gadgets in teaching sport psychology has become increasingly prevalent in tertiary institutions globally, as those gadgets can provide tailored feedback to help athletes improve their performance. This study aims to explore the availability, usability and efficacy of such tools in facilitating the learning of sport psychology in tertiary institutions in the south west, Nigeria, with a focus on their contributions to sustainable global development. Three (3) research Hypotheses were formulated for this study. Purposive sampling technique was used to select twelve tertiary institutions i.e. two (2) from the six south-west States, while the simple random sampling technique was used to select three (3) teaching staff and twenty (20) students from the department of Human Kinetics and Health Education of the sampled institutions, making a total of two hundred and seventy-six (276) respondents. The researcher adopted a mixed-methods approach, incorporating both quantitative surveys and qualitative interviews; the study examines the perspectives of students and educators in tertiary institutions. Self-structured questionnaire with reliability coefficients of 0.75 was used for data collection. Analysis of Variance (ANOVA) was used to analyse the difference between the variables. Findings revealed that technological gadgets for teaching sport psychology are not available in some tertiary institutions, and that the integration of technological gadgets in teaching sport psychology holds significant promise for sustainable global development in tertiary education. Recommendations were made that the government should provide enough of these gadgets for effective use to teach sports psychology, amongst others.